Intellectual Capital dalam Persepsi Nasabah pada Perbankan Syariah di PangkalpinangIntellectual Capital dalam Persepsi Nasabah pada Perbankan Syariah di Pangkalpinang: Intellectual Capital in Customer’s Perception of Sharia Banking in Pangkalpinang - Nizwan Zukhri; Sri Rahayu; Hidayati Hidayati; Erita Rosalina (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2021)
This study investigates the influence of intellectual capital with the dimensions of Human Assets (HC), Structural Capital (SC), and Relationships (RC) on banking performance in the perceptions of customers on Syariah Bank in Pangkalpinang. The choice of method in this research is quantitative with the target of five Sharia banks in Pangkalpinang, namely Bank Syariah Mandiri, BRI Syariah, Bank SumselBabel Syariah, and Bank Muamalat. There were 20 questionnaires distributed in each Sharia bank. The measuring instrument used to calculate the variables is Structure Equation Modeling (SEM). The path coefficient value data processing or path coefficient bootstrapping analysis with the direction of the relationship obtained the human asset variable (HC) results, showing a positive number of 0.361. The structural capital variable (SC) shows a positive number of 0.436, the human asset variable (HC), and the capital variable structural (SC) has a positive effect on banking performance. For the relation variable (RC), the original value showed a positive number of 0.076. The t-statistic value was smaller than the t-value, 0.704 <1.96 so that the relationship variable had no positive effect on banking performance.